Measure of Atopic Dermatitis Disease Severity Using Actigraphy. Issue 1 (January 2014) - Sandoval, Laura F.; Huang, Karen; O'Neill, Jenna L.; Gustafson, Cheryl J.; Hix, Emily; Harrison, Jessica; Clark, Adele; Buxton, Orfeu M.; Feldman, Steven R.
Background: Analyzing adherence to treatment and outcomes in atopic dermatitis is limited by methods to assess continual disease severity. Atopic dermatitis significantly impacts sleep quality, and monitoring sleep through actigraphy may capture disease burden. Purpose: To assess if actigraphy monitors provide continuous measures of atopic dermatitis disease severity and to preliminarily evaluate the impact of a short-course, high-potency topical corticosteroid regimen on sleep quality. Methods: Ten patients with mild to moderate atopic dermatitis applied topical fluocinonide 0.1% cream twice daily for 5 days. Sleep data were captured over 14 days using wrist actigraphy monitors. Investigator Global Assessment (IGA) and secondary measures of disease severity were recorded. Changes in quantity of in-bed time sleep were estimated with random effects models. Results: The mean daily in-bed time, total sleep time, and wake after sleep onset (WASO) were 543.7 minutes (SEM 9.4), 466.0 minutes (SEM 7.7), and 75.0 minutes (SEM 3.4), respectively. WASO, a marker of disrupted sleep, correlated with baseline (ρ = .75) and end of treatment IGA (ρ = .70). Most patients did not have marked changes in sleep. IGA scores declined by a median change of 1 point at days 7 ( p = .02) and 14 ( p = .008). Conclusions: Using actigraphy, atopic dermatitis disease severity positively correlated with sleep disturbances. Actigraphy monitors were well tolerated by this cohort of atopic dermatitis subjects.